Assays to evaluate the transovarial transmission of Anaplasma marginale by Rhipicephalus microplus - Mazzucco Panizza, Matilde Nahimé (2022)
The aim of this study was to evaluate the vectorial competence of Rhipicephalus microplus to transmit Anaplasma marginale transovarially, by analyzing the results of three different but complementary assays. First, larvae of R. microplus were fed on a calf infected with the isolate S1P of A. marginale. The engorged females obtained were analyzed by PCR and incubated for oviposition. After hatching, larvae were analyzed by PCR and fed on susceptible splenectomized cattle. Although A. marginale was detected in the females, no A. marginale DNA was amplified from the larvae and transmission of A. marginale to cattle was not recorded. In the second experiment, R. microplus larvae were fed on cattle naturally infected with field isolates of A. marginale and experimentally infected with the isolate S1P of A. marginale. After detachment, engorged females were incubated for oviposition. The offspring were analyzed by PCR, with negative results. Finally, free-living larvae of R. microplus collected from pasture on farms with cattle infected with A. marginale were analyzed by PCR for Anaplasma infection. All samples analyzed were negative for A. marginale. The results of this work indicate that transovarial transmission of A. marginale by R. microplus is unlikely to occur.